Pengaruh Tingkat Pengetahuan Mahasiswa Terhadap Efek Samping Vaksinasi Covid-19 di Universitas Sari Mulia: Pengaruh Tingkat Pengetahuan Mahasiswa Terhadap Efek Samping Vaksinasi Covid-19 di Universitas Sari Mulia - Darini Kurniawati; Iwan Yuwindry (LPPM Universitas Sari Mulia, 2023)
Background: In general, the side effects that arise after the vaccine vary. In general, mild and temporary and not always there and depending on the condition of the body. Effects such as fever and muscle aches or redness at the injection site are normal but still need to be monitored. The benefits of vaccines far outweigh the risks of getting sick from being infected if not vaccinated. If a Post-Immunization Follow-up Event (KIPI) occurs, it can be reported to the Health Facility where the vaccination is given, then it will be followed up by the focal point in each Health Service and reviewed by the KIPI Study and Management Committee in each region and nationally. To find out how the level of student understanding influences the side effects of the COVID-19 vaccination at Sari Mulia University, Banjarmasin. Objective: Knowing how to influence the level of student understanding of the side effects of COVID-19 vaccination at Sari Mulia University, Banjarmasin. Methods: This study used a descriptive observational cross-sectional design with purposive sampling with inclusion and exclusion criteria set by researchers at Sari Mulia University, Banjarmasin. Data analysis using Naranjo. Results: The results of the research on the incidence rate of drug side effects in the covid-19 vaccine in Sari Mulia University students obtained Probable results as many as 60 respondents, Possible as many as 23 respondents and Doubtful as many as 7 respondents. The results of the statistical analysis of the chi-square test using SPSS. Conclusion: Knowledge questionnaires that have an effect are place of residence, faculty and type of vaccine while age and gender do not affect knowledge. And for the Naranjo questionnaire, the factors that have an effect are the faculty and place of residence, while gender, age and type of vaccine have no effect. The alternative hypothesis (Ha) was accepted because it found that there was an effect on the level of student knowledge on the side effects of the Covid-19 vaccination at Sari Mulia University, Banjarmasin. Meanwhile, the null hypothesis (Ho) was rejected because there was no effect on the level of student knowledge on the side effects of the Covid-19 vaccination at Sari Mulia University, Banjarmasin. Keywords: Vaccines, Knowledge, Naranjo